Final adult height and endocrine complications in young adults with β-thalassemia major (TM) who received oral iron chelation (OIC) in comparison with those who did not use OIC - Soliman, Ashraf T; Yassin, Mohamed A; De Sanctis, Vincenzo (Acta Biomedica Atenei Parmensis, 2018)
Background: Relatively little is known about endocrine function, bone mineral health, and growth during oral iron chelation therapy in β-thalassemia major patients (TM) on treatment with deferasirox. Aims of the study: To study the frequency of endocrine complications, IGF-1 levels and final adult standing height (FA-Ht) in patients with BTM in two groups of adult patients. Patients and methods: The first group (Group A; 15 patients, 6 females and 9 males) received oral iron chelation therapy (OIC) with deferasirox for 6 years before puberty; the second group (Group B;40 patients) attained the FA-Ht before the use of OIC (iron chelation therapy with deferoxamine (DFO) given subcutaneously, since the age of 2 years). In both groups liver iron concentration was measured using FerriScan ® R2-MRI method. Furthermore, the FA-Ht, bode mass index (BMI), and insulin growth factor-1 (IGF-1) in a selected group of adult patients [9 with normal growth hormone (GH) secretion (GHN) and 8 with GH deficiency (GHD; peak GH response to provocative test  with clonidine: < 7 ng/ml), who were on iron chelation therapy with DFO given subcutaneously that was changed to oral deferasirox during the last 5-6 years. These 15 patients were not treated with rhGH. Results: Adults with BTM who received OIC for 6 years or more before attaining their FA-Ht, had lower liver iron concentration (LIC) assessed by FerriScan® R2-MRI, fasting glucose level (FBG) and liver enzymes (ALT and AST), and a better FA-Ht expressed in standard deviation score (FA-Ht-SDS), and higher IGF-1 SDS versus those who did not receive OIC before attaining FA-Ht. The prevalence of endocrinopathies, including hypothyroidism and hypogonadism were significantly lower in Group A versus Group B.  Comparison between the group with normal GHN and those with GHD showed that the FA-Ht-SDS of those with GHD (159.1± 6.42 cm). Ht-SDS = -2.5 ± 0.9) was significantly decreased compared to the group with NGH (Ht = 163.5 ± 5.2 cm, Ht-SDS = -1.74 ± 0.83).  The IGF-1-SDS did not differ between the two groups. Neither ferritin level nor IGF-1 concentrations were correlated with the Ht-SDS. The final FA-Ht-SDS correlated significantly with the peak GH secretion (r = 0.788, p = 0.0008). The FA-Ht-SDS were positively related to their mid-parental height (r=0.58, P